Pemberdayaan Anak Korban Kekerasan Seksual Berbasis Gender melalui Self Efikasi di Jombang - Rofiah, Siti; Jasminto, Jasminto (Proceedings of Annual Conference on Community Engagement, 2018)
This research aimed to find and stimulate self-efficacy of children victims of gender-based sexual violence using the Asset Based Community Development (ABCD) method with the Apreciative Inquiry technique, individual assets and social assets owned by victims of sexual violence. Research findings show that children who are victims of sexual violence are able to accept their condition today, realize their condition and have confidence that they still have success in the future, they will be successful in proving themselves that despite being victims of sexual violence they are able to achieve success in life by continuing school both formal and chase packages, working according to the field of expertise (working in a pharmacy, online business, training in cooking, continuing the business of parents)